Isolation and Classification of Fungal Pathogens of Salvia Rosemary in Different Regions of Al Jabal Al Akhdar - Elham Abdurabbih, (AlQalam Journal of Medical and Applied Sciences, 2025)
Rosemary trees are considered one of the most important natural flora in Libya, which represents the total vegetation cover prevailing in the natural forests of the Green Mountain region, which has currently been subjected to the phenomenon of sudden death, which has led to a change in their density and distribution, threatening their survival. The current study aims to isolate and classify the fungi that cause rosemary diseases in the areas of the Green Mountain, Shahat and Slanta, seeds and stems. Samples were collected from the seeds and stems of the plants in April 2023, on which we found the infection. The samples were retention in sterile bags and retention in refrigerated until they were transported to the laboratory to be analyzed. Types of fungi have appeared10, Aspergillus flavus, Aspergillus niger, Aspergillus fumigates, Aspergillus thermomutants, Alternaria Sp, A.altenate, Apophomyces variabilis Pencillium Sp, Pencillium chrysogenum, Mucer Sp.